STRUCTURE FORMATION PROCESS OF HYDRATED PORTLAND CEMENT COMPOSITIONS: NANOSCALE LEVEL CONTROL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Durability of cement-like construction materials, as well as durability of cement stone, depends on their humidity resistance, frost resistance, corrosion resistance. All of these properties depend not only on the composition of the original clinker, but also on structural organization at micro-and nanoscale level of hydrated portland cement compositions. In this research the authors used the method of small-angle neutron scattering to define structural parameters of hydrated portland cement compositions on nanoscale level, distribution of calcium hydrate silicate nanoparticles in size, medium nanoparticles radius, fractal dimension. It is shown, that introduction of modifying nanoadditives into portland cement compositions affects structural parameters of a cement stone. The following nanoadditives were used: of artificial (alpha aluminium oxide, gamma aluminum oxide) and of anthropogenic (carbonate and alumo-alkaline sludges) origin, as well as integrated nanoadditives containing surfactants. The change in structural parameters of portland cement compositions with nanoadditives in the process of hydration is investigated. It is shown that use of nanoadditives allows to control the process of forming the structure of hydrated portland cement composition on the nanoscale level, directly affect the values of structural parameters and, as a result, modify properties of cement stone.